Galvanizing Nostalgia? : Indigeneity and Sovereignty in Siberia - Balzer, Marjorie Mandelstam (Book collections on Project MUSE., 2021)
"This book explores the survival of federal Russia. Based on the field of cultural anthropology and historical research in the republics of Eastern Siberia--Sakha (Yakutia), Buryatia, and Tyva (Tuva)--the book highlights Indigenous concerns about civil society, spiritual vitality, and ecology. Indigenous groups are defending their lands and rights without being secessionist"--